Long-Term Functional Consequences of Treatment of Fractures of the Distal Metaepiphysis of the Radius - Naumenko, L.Yu.; Mametiev, A.O.; Vinnyk, O.O. (TERRA ORTHOPAEDICA, 2023)
Summary. The frequency of damage to the distal metaepiphysis of the radius reaches from 16% to 33% of all fractures of the bones of the skeleton, and the increase in the incidence  of  osteoporosis  definitely  maintains  the  tendency  to  increase  the  frequency of  damage  to  this  localization.  About  53.3% of  the  injured  need  repositioning;  half of them (26.6%) have large unstable fractures of type B and C, which  are  subject to surgical treatment.Materials and Methods. The study was carried out based on the materials of the trauma centers and trauma departments of the  “City Clinical Hospital No. 2” of the DCC (Dnipro) and the MNPE “City Clinical Hospital No. 6” of the DCC (Dnipro). To assess the long-term consequences, a retrospective  analysis  of  archive records of 318 patients with damage to the distal metaepiphysis of the radius was performed, including 271 radiographs of females (85.2%) and 47 males (14.8%).Results. The conducted analysis gives grounds to  state  that  remote  manifestations depend on the nature and severity of fractures, the quality of reposition or  surgical treatment. Fractures of type A and C have a pronounced tendency  to  develop manifestations of deforming arthrosis of the radiocarpal joint in the remote period after the injury, which may be due to the  presence of  incongruity of  the  articular surfaces against the background of residual “permissible” displacements of the fragments.Conclusions. Ensuring accurate repositioning of fractures and expanding the indications for surgical treatment in case of “permissible” displacement of bone fragments in fractures of the distal metaepiphysis of the radial bone will reduce the frequency and severity of arthrosis in the remote period after the injury.